Modern Monetary Theory: The post-Crisis economy misunderstood? - Chunping Liu; Patrick Minford; Zhirong Ou (Cardiff University, Cardiff Business School, 2022)
We set out Modern Monetary Theory (MMT) as a full DSGE model, and test it by indirect inference on post Financial Crisis US data, alongside a standard New Keynesian, NK, model. The MMT model is rejected, while the NK model has a high probability. We then evaluate replacing the Öscal and monetary policies within the NK model by MMT policies, and Önd that they imply a material loss of welfare.
Keywords: 330; Modern Monetary Theory; DSGE model; Öscal activism; Wald test; indirect inference